Likvärdighet och kvalitet: En studie om förskollärarstudenters verksamhetsförlagda utbildning - Williams, Pia; Sheridan, Sonja; Mellgren, Elisabeth (Educare, 2021)
Swedish preschool teacher profession has changed. In the preschool teacher education, students must develop professional identities and know how to independently take responsibility for pedagogical activities, teaching and providing for children’s right to care, play, development and learning. The aim of this study is twofold: to investigate how students articulate their conditions for learning and professional development in their teaching practice, and to study how their education may be affected by being carried out in preschools of varying quality. The study is based on quality evaluations with the Early Childhood Environment Rating Scale (ECERS) at 153 Swedish preschools. The quality evaluations were related to a survey that 125 students answered in a preschool teacher education focusing on equivalence, the relationship between theory and practice and the quality in their teaching practice. The research questions we posed were: What characterizes the quality of preschools? Which aspects contribute to equality in teaching practice? How do the students describe the quality of the preschool? Bronfenbrenner’s ecological system theory frames the study. The analysis was informed by an interaction between empirical data and theory and thus was an abductive analytical process. The results show that the quality of preschools varies, creating unequal conditions for student learning. The students report inconsistent conditions for their learning in preschool. The political investment has enhanced the collaboration between preschool teacher education and preschool and visualized critical aspects, forming a point of intersection for the preschool teacher profession’s quality.